The Implementation of the Paskibra Program in Developing Students Discipline and Patriotism at SMAN 1 Kota Bima - Fardiansyah, Fardiansyah; Mohammad Mustari; M. Samsul Hadi (JURNAL PENDIDIKAN IPS, 2025)
This study aims to describe the implementation of the Paskibra extracurricular program in developing students’ discipline and patriotism at SMAN 1 Kota Bima, as well as to analyze the impacts of students’ participation in the program. This research employed a descriptive qualitative approach with the subjects being Paskibra members and informants consisting of the principal, supervising teachers, trainers, and alumni. Data were collected through observation, interviews, and documentation. The results of the study indicate that the Paskibra program is carried out through activities such as marching drills, flag-raising ceremonies, leadership training, and the reinforcement of national values. The program was found to be effective in fostering students’ discipline, responsibility, solidarity, leadership, and nationalism. The positive impacts observed include increased awareness of adhering to rules, the development of orderly habits, enhanced self-confidence, improved teamwork skills, and a stronger sense of pride in national symbols. However, the study also identified negative impacts, such as reduced study time due to intensive training schedules, physical fatigue affecting classroom concentration, and psychological pressure on students who struggled to adapt to high disciplinary standards. Overall, the implementation of the Paskibra program makes a significant contribution to shaping students’ discipline and patriotism, although better time management and balanced guidance are needed to minimize the negative impacts